IMPLEMENTASI KEBIJAKAN PENGELOLAAN PENGKAJIAN DAN PENANGANAN KASUS PERTANAHAN DI KOTA PALU - Nurliza, Nurliza (Katalogis, 2015)
This Research Target is know and analyse the Policy Implementation of[is Solving of dispute Land Ground in Palu Town of this Research Type is research qualitative with the informan selected by the four of people. Data collecting use the technique interview and documentation. Technique analyse the data used by that isÂ  (1) Editing (2) Subdividing (3) Interpretation Mean (4) Withdrawal of Conclusion and Suggestion. Result of Research (1) policy Implementation of solving of land;ground dispute in Office of Land;Ground of Palu Town seen from factor of standard and policy target not yet walked better, seen from time duration still in solving of dispute, so that society feel saturated in managing dispute and visit upon the office of Land;Ground of Palu Town. (2) policy Implementation is solving of land;ground dispute in Office of Land;Ground of Palu Town seen from Resource factor not yet walked better this matter is seen from there no fund prepared to the solving of dispute and also medium also not yet adequate. Like there no counter of denunciating of land;ground dispute. (3) policy Implementation is solving of land;ground dispute in Office of Land;Ground of Palu Town seen from factor comunicatioan, characteristic, political and economic social condition and also disposition factor not yet walked better, this matter is seen by that tren of dispute denunciating every year tend to increase later;then facility which disedikan not yet adequateÂ  and also supported by result of interview with the informan conducted by a field telling not yet walked better